GROWTH OF HETEROTROPHIC BACTERIA IN SEA WATER POLLUTED BY SURF DETERGENT - Novan, Dewan Pratama; Effendi, Irwan; Feliatra, Feli (Asian Journal of Aquatic Sciences, 2018)
The research was conducted from February 2016 to April 2017, aimed to determine the effect of adding different concentrations of detergent namely SURF on the growth of bacterial populations in the seawater column. This research used experimental method with Completely Randomized Design. Seawater samples were analyzed at Marine Microbiology Laboratory, Fisheries and Marine Faculty of Riau University. Based on the results of the study, from day 0 untill day 10 after given detergent with different concentrations, bacteria experienced a decreasing trend of growth, in day 15 untill day 20, the trend of bacterial growth contaminated by detergent with different concentration relatively increased to stagnant. Based on the result of this study the addition of different detergent concentration in each treatment affect the growth of heterotrophic bacteria population in the sea water, where the higher concentration of detergent added the lower the ability of bacteria to grow and the ability of heterotrophic bacteria to survive at different concentrations of detergent, it can be concluded that the ability of heterotrophic bacteria to grow from days 0 to 20 has decreased in each of its concentrations